(untitled) (Research, Society and Development, 2021)
Head and neck cancer (CPP) corresponds to assumed tumors in the skin, oral cavity, lips, salivary glands, larynx, pharynx, nasal cavity, paranasal sinuses, external auditory canal and middle ear. It affects people of both sexes, but with greater predilection for males and over 40 years of age. The risk factors associated with this malignancy are smoking, alcohol consumption, overweight, exposure to ultraviolet rays, sedentary lifestyle, among others. Radiotherapy (RT) is the most used treatment for CPP, and consists of different forms of ionizing radiation that act on the DNA of malignant cells in order to cause their death and/or prevent their reproduction. However, although it is in a smaller proportion, due to the greater capacity for regeneration, an RT affects healthy tissues and cells, causing adverse effects that can affect cancer treatment and lead to the patient’s health well-being. Given the above, this study aimed to review the literature on oral manifestations resulting from head and neck radiotherapy and address oral management strategies for head and neck radiotherapy. For the construction of this article, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), National Library of Medicine of the United States (PUBMED) and ScienceDirect databases, using the Mendeley reference manager. The articles were collected from May to August 2021 and covered between 2015 and 2021. From the narrative review of the literature, it was observed that the oral manifestations resulting from radiotherapy of the head and neck xerostomia, oral mucositis, osteoradionecrosis , trismus and dysgeusia. Taking into account the high incidence of PPC, it is extremely important that health professionals are familiarized with the complications arising from cancer treatments.